Synthesis and Characterization of Polyaniline Emeraldine Salt: Tunable Photoluminescence and Optoelectronic Properties for Advanced Applications - Gawbah, Muna A. Bin; Hassan, Elfatih A.; Elshafia, Faiz M.B.; Marouf, Ali A.S. (Journal of Research Updates in Polymer Science, 2025)
Polyaniline emeraldine salt (PANI-ES) is a conductive polymer with promising optoelectronic properties, synthesized via chemical oxidative polymerization and confirmed in its emeraldine salt form through structural analysis. Optical characterization revealed distinct absorption bands linked to key electronic transitions, indicating semiconducting behavior. Under UV excitation, photoluminescence studies showed two main emission features corresponding to dimer and excimer states, both exhibiting large Stokes shifts and a quantum yield of 0.27. These long Stokes shifts suggest efficient energy relaxation, while the moderate quantum efficiency highlights the material’s capability for light-emitting applications. The combination of tunable emission, stable optical response, and electrical conductivity positions PANI-ES as a versatile material for photonic technologies. Potential applications include organic light-emitting diodes (OLEDs), photodetectors, and optically pumped organic lasers. Overall, the study demonstrates that PANI-ES offers a favorable balance of structural stability, optical performance, and electronic properties, making it a strong candidate for integration into advanced optoelectronic and photonic devices.